PENYELESAIAN SENGKETA MELALUI PERADILAN TATA USAHA NEGARA TERHADAP PEMBATALAN KONTRAK LUMPSUM SEPIHAK - Abu Thalhah Al Anshari; Maheswari Queena Dewani; Shintia Januarita; Wilhelmina Setia Atmadja (Collegium Studiosum Journal, 2025)
Another form of potential dispute that wil arise is in the form of a contractual relationship that occurs due to a lump sum contract using a type of construction contract from the government to the private sector. This form can be seen from the inequality of the parties' positions. In practice, "lump sum contracts are often interpreted freely, causing misperceptions between Service Users and Service Providers, such as the words "fixed price" and the sentence "all risks are borne by the service provider". The free perception of "fixed price" means that the price may not be changed at all, no matter what happens. While the perception of the sentence "all risks are borne by the service provider" is wildly interpreted that all risks, including changes at the request of the Service User or due to changes in design, are the full responsibility of the Service Provider. "This can trigger an inequality of justice where in practice the things mentioned above can happen at any time, so the contractor (private) sometimes does not get the fulfillment of the rights to the achievements that have been agreed upon through the contract. The research method used is a normative type of research. The research technique is carried out by adjusting it to the established research approach. For research with the aim of drawing legal principles in a law. The competence of the State Administrative Court as a litigation dispute resolution mechanism for the parties to the case, has the authority to adjudicate administrative disputes included in the object of the State Administrative Decision in this case the form of government action in unilaterally canceling the contract through a state administrative decision issued by an authorized official and has a detrimental impact on the contractor or individual/private legal entity.